2017
DOI: 10.24087/iam.2017.1.8.215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in Vivo Diuretic Activity of Methanolic Extracts of Clutia Abyssinica (Euphorbiaceae) Roots in Wistar Albino Rats

Abstract: Introduction: Most parts of the plant Clutia abyssinica is traditionally used in different diseases because of their medicinal properties. The roots are widely used traditionally, as diuretic purpose, liver problems, enlarged spleen and kidney problems. The present study was carried out to evaluate the diuretic effect of methanolic extracts of Clutia abyssinica roots in rats in comparison with standard drug furosemide. Methodology: Thirty rats of either sex were randomly allocated into five groups of six each.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The delayed diuresis onset with the HME and its EAF and CF may be ascribed due to the slow absorption properties of the responsible active ingredient(s). The long diuresis duration of action with the HME and its EAF and CF throughout the study period (until the 24th hr) may be attributed due to the slow clearance properties of the responsible ingredient(s) [ 27 , 28 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The delayed diuresis onset with the HME and its EAF and CF may be ascribed due to the slow absorption properties of the responsible active ingredient(s). The long diuresis duration of action with the HME and its EAF and CF throughout the study period (until the 24th hr) may be attributed due to the slow clearance properties of the responsible ingredient(s) [ 27 , 28 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Both the roots and leaves are used in the treatment of venereal and skin diseases, chest problems, cancer and fertility in humans. 12 Some scientific studies revealed its in vivo antimalarial, 13 anti-trypanosomal, 14 analgesic, 15 antiinflammatory, 16 antipyretic, 17 diuretic 18 and in vitro antioxidant and anti-proliferative 19 activities. The medicinal value of Clutia abyssinica may be due to its constituents that produce a definite physiological action.…”
Section: Introductionmentioning
confidence: 99%
“…( 25) The CAI effect is disregarded if the Cl -/Na + +K + ratio is between 0.8 and 1.00, but if it is less than 0.8, it is considered to have strong CAI activity. (30) In this study, both M400 and EAF400 exhibited a strong CAI effect with a value of 0.66 and 0.68, respectively. This suggests that M400 and EAF400 might possibly have an inhibiting effect on the renal tubules' carbonic anhydrase enzyme.…”
Section: Discussionmentioning
confidence: 51%